Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/bf03166455
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of polymer films by rf discharge at atmospheric pressure

Abstract: In this contribution we report some typical properties of the discharge which has been used for deposition of thin films and some mechanical parameters of thin films. RF plasma nozzle can burn very well even at atmospheric pressure. Special properties of RF discharges offer hopeful technological applications like deposition of thin solid films. The knowledge of physical parameters of plasma has been required. The parameters of the plasma were investigated by spectral and optical methods. The powered RF electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…1) and that is why it was impossible to realize any measurements. 25 Previous studies 27,28 showed similar values of the measured N e , T e and T g as in this new work.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1) and that is why it was impossible to realize any measurements. 25 Previous studies 27,28 showed similar values of the measured N e , T e and T g as in this new work.…”
Section: Resultssupporting
confidence: 86%
“…1) and that is why there was impossible to realize any measurements [25]. Previous studies [27,28] showed similar values of the measured N e , T e and T g as in this new work. Error bars from the electron number density calculations are 55 approximately ± 15 %.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Applications include surface cleaning, surface activation, film deposition and the reduction of micro-organisms [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The convenience for special polymer lm deposition has also been proven. 4 It has been further tested as an alternative excitation source for elemental analysis of liquids. 5 The analytical prot of the plasma pencil has been shown during the determination of Li, Na, Mg, Ca, Cu and Zn in aqueous solutions as representatives of alkali, alkali-earth and transition metals.…”
Section: Introductionmentioning
confidence: 99%